TINDAK TUTUR BAHASA INGGRIS DALAM PENERAPAN TEKNIK ROLE PLAY PADA MAHASISWA JURUSAN KANTOR DEPAN PPLP MAPINDO - Paramita Sari, Ni Luh Komang Julyanti (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2015)
This research focuses on learning to speak by using role-play technique which was applied to students major in front office department of PPLP MAPINDO. The subject that was examined in this study is the use of speech acts used by students majoring in the front office department of PPLP MAPINDO in the application of role play technique during the learning process. Based on analysis it was found that the students used some forms of speech they are; locutionary act, illocutionary act, perlocutionary act, directly literal speech act, indirect literal speech act, directly speech acts not literal, maxim of quantity, maxim quality, maxim of relation, maxims of manner, maxims of wisdom, maxim of generosity, maxim of appreciation, maxim of simplicity, maxim of agreement and maxim of sympathy.
Keywords: speaking, role play, speech act, English